Remain in Sight: Displaying Availability as a Bystander Salesperson to (Re-) initiate Talk with Customers - Hiramoto, Takeshi (Social Interaction. Video-Based Studies of Human Sociality, 2026)
This study investigates how salespeople in Japanese bedding retail stores establish interactional space as a resource for (re-)initiating sales talk. Drawing on multimodal conversation analysis of video-recorded service encounters, the paper documents the practice of remaining: salespeople staying at the spot where an initial sales pitch has been made—even when the attempt fails. Remaining displays their availability as bystander participants by configuring an object-focused interactional space. The analysis shows that salespeople (1) time their approach when customers engage in object-focused activities, (2) remain in the area of a failed pitch, (3) adjust their bodily orientation to stand just outside customer focus, and (4) display availability by standing and doing nothing. These practices demonstrate that remaining is not passive, but a socio-spatial accomplishment that supports subsequent sales interaction. The findings contribute to conversation analytic research on service encounters by explicating how “roaming” salespeople enact organizational goals through embodied practices.